Trends in prevalence of substance use among Icelandic adolescents, 1995–2006 - Sigfusdottir, Inga D (BioMed Central, 2008)
BACKGROUND: Adolescent substance use continues to be of great global public health concern in many countries with advanced economies. Previous research has shown that substance use among 15–16 year-old-youth has increased in many European countries in recent years. The aim of this study was to examine trends in prevalence of daily smoking, alcohol intoxication, and illicit substance use among Icelandic adolescents. METHODS: Repeated-measures, population-based cross-sectional surveys of between 3,100 and 3,900 10th-grade students who participated in the annual Youth of Iceland studies were analyzed, with response rates of between 80% and 90%. RESULTS: The prevalence of daily smoking, alcohol intoxication, and illicit substance use was at a peak in 1998, with almost 23% having reported daily smoking, 42% having reported becoming intoxicated at least once during the last 30 days, and over 17% having used hashish once or more often in their lifetime. By 2006, daily smoking had declined to 12%, having become intoxicated once or more often during the last 30 days to 25%, and having ever used hashish declined to 9%. CONCLUSION: The prevalence of substance use among Icelandic 10(th )graders declined substantially from 1995 to 2006. Proportions of adolescents who smoke cigarettes, had become intoxicated during the last 30 days, as well as those admitting to hashish use all decreased to a great deal during the period under study. The decline in prevalence of adolescent substance use in Iceland is plausibly the result of local community collaboration where researchers, policy makers and practitioners who work with young people have combined their efforts.